ENDOGENOUS ROYALTY FACTOR IN A LICENSING CONTRACT - Buratto, Allesandra; Grosset, Luca; Viscolani, Bruno (Yugoslav Journal of Operations Research, 2016)
The owner of a well known fashion brand grants a manufacturer the rights to produce and sell a second-line brand against a percentage of the sales calledroyalty. Tothisend,thebrandownerandthemanufacturersignalicensing contract which assigns the owner, who has already determined his advertising campaign, the right of determining the royalty factor. The manufacturer will plan her advertising campaign for the licenced product in order to maximize her proﬁt. The brand owner’s objective is twofold: on the one hand, he wants to maximize the proﬁt coming from the contract, on the other hand, he wants to improve the value of the brand at the end of a given planning period. We model this interaction between the two agents using a Stackelberg game, where the brand owner is the leader and the manufacturer is the follower. We characterise the royalty percentage and the licensee’s advertising eﬀort which constitute the unique Stackelberg equilibrium of the game.